PROSPECTIVE TEACHERS’ EXPERIENCES OF USING VIDEO AND PHOTOVOICE FOR REFLECTION IN MICROTEACHING - Devi Novitasari; Abd. Rahman; Dian Arief Pradana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study explored prospective teachers’ experiences using reflective practice tools: video and photovoice. Five prospective students comprising two males and three females aged between 21-24 voluntarily participated in the present study. All participating students were required to submit eight reflective journals mediated by video of their teaching and eight photovoice-based reflective journals during microteaching. At the end, multiple informal interviews were held to investigate participating students’ experiences of their reflection through video and photovoice. The findings of the study showed that the prospective teachers generally perceived photovoice-based reflection more fruitful than video stimulated reflection. Timing, specificity, and simplicity were the major reasons of preference.